Digital addiction among young adolescent: mitigating the Impact of media technological adversity - Muhammad Ashraf, Fauzi; Noor Suhani, Sulaiman; Nur Muneerah, Kasim; Siti Aminah, Harun (IOP Publishing, 2020)
Addiction toward social media has become a new norm, especially among young adolescent. Social media users in Malaysia accounted to nearly 20 million, more than half of the population. Some individual having more than one account in different social media platform. With the increasing prevalent of social media addiction among young adolescent, this study ought to identify what are the critical factors that can influence one addiction toward social media. Based on the technology acceptance model (TAM) and flow-happiness theory, this study would like to unfold this issue and connect the possible factors that play critical role in user's social media addiction based on its detrimental impact. Using partial least square structural equation modelling (PLS-SEM), this study applies the quantitative study by testing the antecedents of social media addition. 217 respondents who are mainly university students responded to the survey. It was found that the most critical factor is perceived ease of use on perceived usefulness and subsequently attitude. The second most critical path is user's enjoyment toward satisfaction. Surprisingly, perceived usefulness towards habit and attitude toward social media addiction itself was not significant. This study would help practitioners to implement mitigating strategy to reduce social media addiction young adolescent, especially those who studying in school and higher education institution.